Hubungan antara kebiasaan membaca buku komik dengan kemampuan mengarang siswa kelas X SMK PGRI 16 Jakarta Timur - Yayan Sudrajat; Maman Paturahman (Asosiasi Dosen Pemerhati Pendidikan Indonesia, 2022)
The purpose of this study was to determine the relationship between the habit of reading comic books with the writing ability of class X students of SMK PGRI 16 East Jakarta. The research method used is a quantitative research method. Based on data analysis and hypothesis testing, it is known that there is a significant relationship between reading habits of comic books and writing skills of students in class X SMK PGRI 16 East Jakarta. This is because based on the results of the t-test, it is obtained that tcount = 8.219 > ttable = 2.0252. The two variables are strongly correlated. That's because based on the results of the correlation analysis obtained r = 0.80. This relationship is categorized as high/strong because it is in the range between 0.60 – 0.80. The contribution of the habit of reading comic books to the writing ability of students in class XI SMK PGRI 16 East Jakarta is 64%. Keywords: Reading comic book, Writing skill